Visual attention and recall of flavored cigarillo package elements among young adults: A randomized control trial. - Stephanie Pike Moore; Alysha C Ennis; Sho Kirihara; Elvia C Gomez; Maya Reyes-Klein; Hannah Sharp; Joseph M Macisco; Erika S Trapl; Amanda J Quisenberry; Elizabeth G Klein (Public Library of Science (PLoS), 2024)
Introduction Flavoring in cigarillos contributes to greater product initiation and abuse liability particularly among young adults. Few studies have examined how packaging elements, including flavor, may draw visual attention from potential consumers as well as impact product recall. This study aimed to test the difference in visual attention to flavor names and other packaging elements on cigarillo products as well as recall of these packaging elements. Materials and methods Young adults aged 16-28 years were recruited to participate in a randomized control trial (Clinictrials.org ID: NCT04358705) in June through December 2022 (N = 89). Participants were randomized to two conditions viewing 12 flavored or unflavored cigarillo package images. Eye tracking software captured participants viewing (dwell) time on package features: flavor, brand, health warning, price, and other package imagery. Participants were asked about their recall of the images viewed. The proportion of dwell time on each package elements were used to examine differences between experimental conditions. Results Across conditions, participants spent the greatest proportion of dwell time looking at the health warning. Participants in the flavored condition spent a significantly greater proportion of dwell time looking at flavor name (mean: 10.66%; SD: 3.56) compared to those in the unflavored condition (mean:7.03%; SD 2.81). Following the experiment, 45.8% of those in the flavored condition recalled having seen flavors or flavor names, which was greater than recall of all other elements and was significantly greater than flavor recall in the unflavored condition (12.2%). Conclusions Flavored cigarillos attract greater visual attention and were the most memorable element of cigarillo packaging among young adults sampled. Changes to cigarillo packaging, including limiting flavor descriptors, imagery, and/or color on packaging and advertisements may be an effective way to reduce young adults' attention to the products and thus their appeal.